Minimal Surfaces in Standard Three-Dimensional Geometry Sol3 - Masaltsev, L. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
We study minimal and totally geodesic surfaces in the standart three-dimensional geometry Sol^3 with the left-invariant metric ds^2=e^2zdx^2+e^-2zdy^2+dz^2. Mathematics Subject Classification: 53A10, 53C42.